(untitled) (Scientific journal of the Fergana State University, 2025)
The article provides a general description of the historically formed sandy areas of the Fergana Valley. The geomorphological characteristics of the sandy areas, climatic conditions and biological diversity, as well as environmental problems arising from anthropogenic impact are analyzed. The research results show that it is necessary to take the necessary measures for sustainable management of sandy areas, strengthen environmental monitoring, combat deflation, and soil erosion.